A method for preparing high-efficiency light-absorbing heating fibers containing inorganic powder of alloy containing silicon based on polyester

CN123005545APending Publication Date: 2026-10-30ZHEJIANG JINCAI NEW MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610127115.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-29
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

本发明通过三层同轴纺丝,以聚酯切片作为皮层,NiCuAgWCo-MoS2纳米粉体和聚酯切片作为中间纺丝层,液态金属镓铟作为芯层,制备得到具有三层纺丝结构的高效吸光发热聚酯纤维。本发明制备得到的高效吸光发热聚酯纤维同时兼具较好的吸光发热性能以及机械性能。具体地:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a method for preparing high-efficiency light-absorbing and heat-generating polyester fibers containing alloy inorganic powder based on polyester, and belongs to the technical field of functional materials. The high-efficiency light-absorbing and heat-generating polyester fibers with a three-layer spinning structure are prepared by three-layer coaxial spinning, taking polyester chips as a skin layer, taking NiCuAgWCo-MoS2 nano-powder and polyester chips as an intermediate spinning layer, and taking liquid metal gallium-indium as a core layer. The high-efficiency light-absorbing and heat-generating polyester fibers prepared by the application have good light-absorbing and heat-generating performance and mechanical performance simultaneously.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing high-efficiency light-absorbing and heat-generating fibers based on polyester containing rice alloy inorganic powder, belonging to the field of functional materials technology. Background Technology

[0002] Polyester materials (polyethylene terephthalate, PET) are widely used in fibers, films, and plastic products due to their excellent mechanical properties, chemical resistance, and processing performance. However, traditional polyester materials have shortcomings in light absorption and heat generation, which limits their application in some specific fields.

[0003] Conventional methods to improve the heat absorption and luminescence properties of polyester materials include adding inorganic functional powders, core-shell structure design, introducing other polymers, improving processes, and surface treatment. Adding inorganic functional powders (such as carbon black) enhances the light absorption and heat generation properties by adding inorganic functional powders to the polyester. However, inorganic powders tend to agglomerate in high-viscosity polyesters, leading to poor fiber spinnability. Furthermore, relying solely on physical blending results in insufficient bonding between the powder and the polyester matrix, affecting the light absorption and heat generation efficiency.

[0004] Core-shell structure design combines a light-absorbing and heat-generating material with a far-infrared radiating material. The light-absorbing and heat-generating material absorbs light energy and transfers heat to the far-infrared radiating material through thermal conduction. However, the fabrication process of core-shell structures is complex and requires high material uniformity and stability. Introducing other polymers, such as polyethers, can affect mechanical properties. Therefore, there is an urgent need for a polyester material that has a simple preparation process, good durability, and high efficiency in light absorption and heat generation. Summary of the Invention

[0005] [Technical Issues] Existing polyester materials have poor light absorption and heat generation properties, as well as poor mechanical properties.

[0006] [Technical Solution] This invention utilizes a three-layer coaxial spinning process, employing polyester chips as the sheath, NiCuAgWCo-MoS2 nanoparticles and polyester chips as the intermediate spinning layer, and liquid gallium indium as the core layer, to prepare a high-efficiency light-absorbing and heat-generating polyester fiber with a three-layer spinning structure. The high-efficiency light-absorbing and heat-generating polyester fiber prepared by this invention possesses both good light absorption and heat generation properties and mechanical properties.

[0007] The first objective of this invention is to provide a method for preparing high-efficiency light-absorbing and heat-generating polyester fibers containing nano-alloy inorganic powders, comprising the following steps: Polyester chips are melted to obtain a skin spinning solution; polyester chips and NiCuAgWCo-MoS2 nanoparticles are mixed at a mass ratio of 10:2~3 and melted to obtain an intermediate layer spinning solution; liquid gallium indium is used as a core layer spinning solution; the skin layer spinning solution, intermediate layer spinning solution and core layer spinning solution are coaxially spun in three layers and dried to obtain a high-efficiency light-absorbing and heat-generating polyester fiber. The preparation method of NiCuAgWCo-MoS2 nanopowder is as follows: (1) Dissolve nickel sulfate, copper sulfate, and cobalt sulfate in an aqueous ethylene glycol solution, heat the solution, and then add silver sulfate and tungsten sulfate in sequence and disperse them evenly to obtain a mixed solution; wherein the molar ratio of nickel sulfate, copper sulfate, silver sulfate, tungsten sulfate, and cobalt sulfate is 1~1.2:1:0.04~0.05:0.03~0.04:1~1.2; (2) The mixed solution undergoes a hydrothermal reaction. After the reaction, the product is collected, washed, and dried to obtain a mixture. (3) The mixture is ball-milled, and then layered molybdenum disulfide is added and ball-milled. After ball milling, it is washed and dried to obtain precursor powder; (4) The precursor powder was sintered, cooled, ground and sieved to obtain NiCuAgWCo-MoS2 high-entropy alloy powder; The ratio of the total mass of nickel sulfate, copper sulfate, silver sulfate, tungsten sulfate, and cobalt sulfate to the amount of ethylene glycol aqueous solution and layered molybdenum disulfide is 0.8~1.2g:1~2mL:4~6g.

[0008] In one embodiment, in step (1), after heating to 55~65°C, silver sulfate and tungsten sulfate are added sequentially; the ethylene glycol aqueous solution in step (1) is prepared by ethylene glycol and water in a volume ratio of 1:1.

[0009] In one embodiment, the hydrothermal reaction in step (2) is carried out at 180~200℃ for 18~22h; the ball milling in step (3) is carried out at 500~550rpm for 10~12h under argon conditions, followed by the addition of layered molybdenum disulfide and continued ball milling for 5~6h.

[0010] In one embodiment, the sintering in step (4) is carried out under vacuum conditions by raising the furnace temperature to 350-380°C at a heating rate of 1-15°C / min and holding it for 2.5-3 hours; then the temperature is raised to 400-450°C and held for 40-50 minutes.

[0011] In one embodiment, the propulsion speeds of the skin spinning solution, the intermediate layer spinning solution, and the core layer spinning solution are 0.4~0.5 mL / min, 0.9~1.0 mL / min, and 0.4~0.5 mL / min, respectively.

[0012] In one embodiment, polyester chips and NiCuAgWCo-MoS2 nanoparticles in the intermediate layer spinning solution are in a mass ratio of 10:2~3.

[0013] A second objective of this invention is to provide a high-efficiency light-absorbing and heat-generating polyester fiber prepared by any of the methods described above.

[0014] A third objective of this invention is to provide the application of the above-mentioned high-efficiency light-absorbing and heat-generating polyester fiber in the preparation of light-absorbing and heat-generating materials.

[0015] The fourth objective of this invention is to provide a method for simultaneously improving the mechanical strength and light absorption and heat dissipation properties of polyester fibers. This method utilizes NiCuAgWCo-MoS2 nanoparticles to prepare highly efficient light-absorbing and heat-dissipating polyester fibers, with the following steps: Polyester chips are melted to obtain a skin spinning solution; polyester chips and NiCuAgWCo-MoS2 nanoparticles are mixed at a mass ratio of 10:2~3 and melted to obtain an intermediate layer spinning solution; liquid gallium indium is used as a core layer spinning solution; the skin layer spinning solution, intermediate layer spinning solution and core layer spinning solution are coaxially spun in three layers and dried to obtain a high-efficiency light-absorbing and heat-generating polyester fiber. The preparation method of NiCuAgWCo-MoS2 nanopowder is as follows: (1) Dissolve nickel sulfate, copper sulfate, and cobalt sulfate in an aqueous ethylene glycol solution, heat the solution, and then add silver sulfate and tungsten sulfate in sequence and disperse them evenly to obtain a mixed solution; wherein the molar ratio of nickel sulfate, copper sulfate, silver sulfate, tungsten sulfate, and cobalt sulfate is 1~1.2:1:0.04~0.05:0.03~0.04:1~1.2; (2) The mixed solution undergoes a hydrothermal reaction. After the reaction, the product is collected, washed, and dried to obtain a mixture. (3) The mixture is ball-milled, and then layered molybdenum disulfide is added and ball-milled. After ball milling, it is washed and dried to obtain precursor powder; (4) The precursor powder was sintered, cooled, ground and sieved to obtain NiCuAgWCo-MoS2 high-entropy alloy powder; The ratio of the total mass of nickel sulfate, copper sulfate, silver sulfate, tungsten sulfate, and cobalt sulfate to the amount of ethylene glycol aqueous solution and layered molybdenum disulfide is 0.8~1.2g:1~2mL:4~6g.

[0016] In one embodiment, in step (1), after heating to 55~65°C, silver sulfate and tungsten sulfate are added sequentially; the ethylene glycol aqueous solution in step (1) is prepared by ethylene glycol and water in a volume ratio of 1:1.

[0017] In one embodiment, the hydrothermal reaction in step (2) is carried out at 180~200℃ for 18~22h; the ball milling in step (3) is carried out at 500~550rpm for 10~12h under argon conditions, followed by the addition of layered molybdenum disulfide and continued ball milling for 5~6h.

[0018] In one embodiment, the sintering in step (4) is carried out under vacuum conditions by raising the furnace temperature to 350-380°C at a heating rate of 1-15°C / min and holding it for 2.5-3 hours; then the temperature is raised to 400-450°C and held for 40-50 minutes.

[0019] In one embodiment, the propulsion speeds of the skin spinning solution, the intermediate layer spinning solution, and the core layer spinning solution are 0.4~0.5 mL / min, 0.9~1.0 mL / min, and 0.4~0.5 mL / min, respectively.

[0020] In one embodiment, polyester chips and NiCuAgWCo-MoS2 nanoparticles in the intermediate layer spinning solution are in a mass ratio of 10:2~3.

[0021] [Beneficial Effects] This invention utilizes a three-layer coaxial spinning process, employing polyester chips as the sheath, NiCuAgWCo-MoS2 nanoparticles and polyester chips as the intermediate spinning layer, and liquid gallium indium as the core layer, to prepare a high-efficiency light-absorbing and heat-generating polyester fiber with a three-layer spinning structure. The high-efficiency light-absorbing and heat-generating polyester fiber prepared by this invention possesses both good light-absorbing and heat-generating properties and mechanical properties. Specifically: The fiber prepared by this invention has a temperature change of over 21°C, a breaking strength of over 49 CN / Tex, and a breaking elongation of over 43%. Detailed Implementation

[0022] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explanation of the present invention and are not intended to limit the present invention.

[0023] Test method: Light absorption and heat generation performance test: Indoor far-infrared lamps were used for testing. Test conditions: 150W infrared light source, receiving distance of approximately 45cm, illumination time of 10 minutes and a 5-minute interval between illumination and light exposure. The light source illuminated the fiber surface, and an infrared thermometer was used to detect and record the temperature change of the sample surface. Tensile elongation at break and tensile strength: According to GB / T3923.1 The 2013 standard for textiles, fiber elongation and tensile breaking strength was adopted.

[0024] Wash resistance: The high-efficiency photothermal heating and heat-insulating functional fibers were subjected to 50 wash cycles using a standard washing machine and phosphate-free detergent, with samples dried after each wash. After every 10 washes, the tensile strength of the samples was tested using a tensile testing machine according to ASTM D2256, and their photothermal heating performance was evaluated.

[0025] Raw materials used in the examples: The materials and polyester chips used in the examples are all commercially available; The preparation method of layered molybdenum disulfide is as follows: 4.3 g of sodium molybdate and 3.3 g of sodium sulfide were dissolved in 70 mL of distilled water and magnetically stirred at 60 °C to obtain a solution with a sodium molybdate concentration of 0.06 g / mL, a sodium sulfide concentration of 0.05 g / mL, and a molar ratio of molybdenum atoms to sulfur atoms of 1:2. 2 mL of HNTs powder at 100 °C was added to the mixture, and stirring was continued until the solid and liquid were homogeneous. The mixture was then transferred to a stainless steel high-pressure reactor lined with polytetrafluoroethylene and reacted at 240 °C and 15 rpm for 12 h. After the reaction, the system was allowed to cool naturally to room temperature. The product was washed with a 40% (w / w) aqueous solution of hydrofluoric acid and a 38% (w / w) aqueous solution of hydrochloric acid to remove the template. It was then washed three times with deionized water and anhydrous ethanol, centrifuged, filtered, dried at 80 °C for 24 h, ground, and the product was collected. The prepared MoS2 was a stacked sheet-like structure with five layers.

[0026] Example 1 A method for preparing high-efficiency light-absorbing and heat-generating polyester fibers containing nano-alloy inorganic powders includes the following steps: Polyester chips are melted at 200°C to form a skin spinning solution; Polyester chips and NiCuAgWCo-MoS2 nanoparticles were added to a high-speed mixer at a mass ratio of 10:2 and premixed for 5 minutes. Then they were melted at 200℃ to form an intermediate layer spinning solution. Liquid gallium-indium alloy is used as the core spinning solution; The sheath spinning solution, intermediate layer spinning solution, and core layer spinning solution were respectively loaded into three syringes for coaxial spinning of the three layers. The feed rates of the sheath spinning solution, intermediate layer spinning solution, and core layer spinning solution were 0.5 mL / min, 1.0 mL / min, and 0.4 mL / min, respectively. After drying, high-efficiency light-absorbing and heat-generating polyester fiber was obtained. The preparation method of NiCuAgWCo-MoS2 nanopowder includes the following steps: (1) Dissolve nickel sulfate, copper sulfate and cobalt sulfate in an aqueous ethylene glycol solution (ethylene glycol and water volume ratio 1:1), then heat to 60°C and add silver sulfate to mix, then add tungsten sulfate and disperse evenly to obtain a mixed solution; (2) The mixed solution was hydrothermally reacted at 190°C for 20 h; after the reaction was completed, the product was collected, washed with water, and dried at 60°C for 10 h to obtain the mixture; (3) The mixture was placed in a ball mill jar and ball milled at 500 rpm for 12 h under argon conditions; then layered molybdenum disulfide was added and ball milling continued for 6 h. After ball milling, the mixture was washed with water and dried at 60 °C for 4 h to obtain precursor powder. (4) The precursor powder was placed in a vacuum sintering furnace and the furnace temperature was raised to 350°C at a heating rate of 10°C / min and held for 3 hours. The temperature was then raised to 450°C and held for 40 minutes. The powder was cooled to room temperature, ground, and sieved to obtain NiCuAgWCo-MoS2 high entropy alloy powder with a particle size of 5-10 μm.

[0027] The ratio of total mass (nickel sulfate, copper sulfate, silver sulfate, tungsten sulfate, cobalt sulfate), ethylene glycol aqueous solution, and layered molybdenum disulfide is 1g:1.5mL:5g. The molar ratio of nickel sulfate, copper sulfate, silver sulfate, tungsten sulfate, and cobalt sulfate is 1:1:0.05:0.03:1; the particle size of the layered molybdenum disulfide is 2 μm.

[0028] Example 2 The mass ratio of polyester chips and NiCuAgWCo-MoS2 nanoparticles in Example 1 was adjusted to 10:3, while other aspects remained the same as in Example 1, to obtain fibers.

[0029] Example 3 In Example 1, the feed rates of the sheath spinning solution, intermediate layer spinning solution, and core layer spinning solution were adjusted to 0.4 mL / min, 0.9 mL / min, and 0.5 mL / min, respectively; all other parameters remained the same as in Example 1, and fibers were obtained.

[0030] Comparative Example 1 The NiCuAgWCo-MoS2 nanopowder in Example 1 was omitted, while everything else remained the same as in Example 1, resulting in fibers.

[0031] Comparative Example 2 The NiCuAgWCo-MoS2 nanopowder in Example 1 was replaced with nano-carbon black, while other aspects remained the same as in Example 1, resulting in fibers.

[0032] Comparative Example 3 The sheath spinning solution and the intermediate layer spinning solution from Example 1 were combined to perform spinning of a two-layer structure consisting of a sheath and a core layer. Everything else remained the same as in Example 1 to obtain fibers.

[0033] Comparative Example 4 NiCuAgWCo-MoS2 nanoparticles and liquid metal were mixed to form a core spinning solution; the middle layer of NiCuAgWCo-MoS2 nanoparticles was omitted; and other aspects remained the same as in Example 1 to obtain fibers.

[0034] Comparative Example 5 NiCuAgWCo-MoS2 nanoparticles, liquid metal, and polyester chips were directly mixed and spun together, with other steps remaining the same as in Example 1, to obtain fibers.

[0035] The obtained fibers were subjected to performance tests, and the test results are as follows: Table 1

[0036] Table 2 Data after washing

[0037] The results showed that the properties of the prepared fibers were poor when the type of powder or the spinning method was changed.

[0038] Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Anyone skilled in the art can make various modifications and alterations without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be determined by the claims.

Claims

1. A method for preparing high-efficiency light-absorbing and heat-generating polyester fibers containing nano-alloy inorganic powder, characterized in that, Including the following steps: Polyester chips are melted to obtain a skin spinning solution; polyester chips and NiCuAgWCo-MoS2 nanoparticles are mixed at a mass ratio of 10:2~3 and melted to obtain an intermediate layer spinning solution; liquid gallium indium is used as a core layer spinning solution; the skin layer spinning solution, intermediate layer spinning solution and core layer spinning solution are coaxially spun in three layers and dried to obtain a high-efficiency light-absorbing and heat-generating polyester fiber. The preparation method of NiCuAgWCo-MoS2 nanopowder is as follows: (1) Dissolve nickel sulfate, copper sulfate, and cobalt sulfate in an aqueous ethylene glycol solution, heat the solution, and then add silver sulfate and tungsten sulfate in sequence and disperse them evenly to obtain a mixed solution; wherein the molar ratio of nickel sulfate, copper sulfate, silver sulfate, tungsten sulfate, and cobalt sulfate is 1~1.2:1:0.04~0.05:0.03~0.04:1~1.2; (2) The mixed solution undergoes a hydrothermal reaction. After the reaction, the product is collected, washed, and dried to obtain a mixture. (3) The mixture is ball-milled, and then layered molybdenum disulfide is added and ball-milled. After ball milling, it is washed and dried to obtain precursor powder; (4) The precursor powder was sintered, cooled, ground and sieved to obtain NiCuAgWCo-MoS2 high-entropy alloy powder; The ratio of the total mass of nickel sulfate, copper sulfate, silver sulfate, tungsten sulfate, and cobalt sulfate to the amount of ethylene glycol aqueous solution and layered molybdenum disulfide is 0.8~1.2g:1~2mL:4~6g.

2. The method according to claim 1, characterized in that, In step (1), after heating to 55~65℃, silver sulfate and tungsten sulfate are added in sequence; the ethylene glycol aqueous solution in step (1) is prepared by ethylene glycol and water in a volume ratio of 1:

1.

3. The method according to claim 1, characterized in that, In step (2), the hydrothermal reaction is carried out at 180~200℃ for 18~22h; in step (3), the ball milling is carried out at 500~550rpm for 10~12h under argon gas, and then layered molybdenum disulfide is added and the ball milling continues for 5~6h.

4. The method according to claim 1, characterized in that, In step (4), sintering is carried out under vacuum conditions, with the furnace temperature raised to 350-380℃ at a heating rate of 1-15℃ / min and held for 2.5-3h; then the temperature is raised to 400-450℃ and held for 40-50min.

5. The method according to claim 1, characterized in that, The propulsion speeds of the cortex spinning solution, the intermediate layer spinning solution, and the core layer spinning solution are 0.4~0.5 mL / min, 0.9~1.0 mL / min, and 0.4~0.5 mL / min, respectively.

6. The method according to claim 1, characterized in that, Polyester chips and NiCuAgWCo-MoS2 nanoparticles in the intermediate spinning solution are mixed at a mass ratio of 10:2~3.

7. The high-efficiency light-absorbing and heat-generating polyester fiber prepared by the method according to any one of claims 1 to 6.

8. The application of the high-efficiency light-absorbing and heat-generating polyester fiber according to claim 7 in the preparation of light-absorbing and heat-generating materials.

9. A method for simultaneously improving the mechanical strength and light absorption and heat dissipation properties of polyester fibers, characterized in that, The high-efficiency light-absorbing and heat-generating polyester fiber was prepared using NiCuAgWCo-MoS2 nanoparticles, and the steps are as follows: Polyester chips are melted to obtain a skin spinning solution; polyester chips and NiCuAgWCo-MoS2 nanoparticles are mixed at a mass ratio of 10:2~3 and melted to obtain an intermediate layer spinning solution; liquid gallium indium is used as a core layer spinning solution; the skin layer spinning solution, intermediate layer spinning solution and core layer spinning solution are coaxially spun in three layers and dried to obtain a high-efficiency light-absorbing and heat-generating polyester fiber. The preparation method of NiCuAgWCo-MoS2 nanopowder is as follows: (1) Dissolve nickel sulfate, copper sulfate, and cobalt sulfate in an aqueous ethylene glycol solution, heat the solution, and then add silver sulfate and tungsten sulfate in sequence and disperse them evenly to obtain a mixed solution; wherein the molar ratio of nickel sulfate, copper sulfate, silver sulfate, tungsten sulfate, and cobalt sulfate is 1~1.2:1:0.04~0.05:0.03~0.04:1~1.2; (2) The mixed solution undergoes a hydrothermal reaction. After the reaction, the product is collected, washed, and dried to obtain a mixture. (3) The mixture is ball-milled, and then layered molybdenum disulfide is added and ball-milled. After ball milling, it is washed and dried to obtain precursor powder; (4) The precursor powder was sintered, cooled, ground and sieved to obtain NiCuAgWCo-MoS2 high-entropy alloy powder; The ratio of the total mass of nickel sulfate, copper sulfate, silver sulfate, tungsten sulfate, and cobalt sulfate to the amount of ethylene glycol aqueous solution and layered molybdenum disulfide is 0.8~1.2g:1~2mL:4~6g.

10. The method according to claim 9, characterized in that, The propulsion speeds of the cortex spinning solution, the intermediate layer spinning solution, and the core layer spinning solution are 0.4~0.5 mL / min, 0.9~1.0 mL / min, and 0.4~0.5 mL / min, respectively.